Studi Living Hadis Kebiasaan Membaca Surat al-Mulk Setiap ba’da Salat Isya di Masjid Al-Mukhlisin Perumnas Mandala - Ikhsan, Muhammad Fazaru; Yuslem, Nawir (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The tradition of practicing hadith in daily life is a manifestation of living hadith, demonstrating the connection between normative texts and the religious practices of Muslim communities. One concrete manifestation of this phenomenon is the habit of reciting Surah Al-Mulk after every Isha prayer, consistently practiced by the congregation of the Al-Mukhlisin Mosque in Perumnas Mandala. This habit is interesting to study because it reflects the internalization of hadith-based Islamic values, particularly those related to the virtue of Surah Al-Mulk in providing intercession and protection in the grave. This study aims to determine the form of implementation, motivation, and spiritual and social values contained in this habit. The method used is a qualitative living hadith approach through participatory observation, in-depth interviews, and documentation of practitioners. The results show that the habit of reciting Surah Al-Mulk is carried out in congregation after Isha prayer, led by an imam or appointed congregation. This activity is not only an individual act of worship, but also strengthens Islamic brotherhood among congregants, increases enthusiasm for Quranic study, and serves as a means of collectively internalizing the Prophet's teachings. The majority of congregants stated that this practice fosters a sense of calm, increases spiritual motivation, and serves as a role model across generations, especially for children and adolescents. In conclusion, this practice reflects a living hadith that strengthens the spiritual, social, and educational dimensions of religious life and is worthy of development in other mosques as part of cultivating Quranic values.